2016
DOI: 10.1002/chem.201504530
|View full text |Cite
|
Sign up to set email alerts
|

Merging Visible‐Light Photocatalysis and Palladium Catalysis for C−H Acylation of Azo‐ and Azoxybenzenes with α‐Keto Acids

Abstract: An efficient C-H acylation of azo- and azoxybenzenes with α-keto acids has been developed by a combination of palladium catalysis and visible-light photoredox catalysis at room temperature under 1.5 W blue LED irradiation. This method tolerates a variety of disubstituted azo- and azoxybenzenes, as well as α-keto acids regardless of the nature of the substituents. A number of aryl ketones were obtained in good yields under mild reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(42 citation statements)
references
References 89 publications
0
38
0
2
Order By: Relevance
“…119 In addition, Wang and co-workers revealed that aryl ketones can be generated by combining photoredox-mediated acyl radical generation with directed Pd-catalyzed C–H activation. 120 …”
Section: Metallaphotoredox Catalysis: C–c Bond Formationmentioning
confidence: 99%
“…119 In addition, Wang and co-workers revealed that aryl ketones can be generated by combining photoredox-mediated acyl radical generation with directed Pd-catalyzed C–H activation. 120 …”
Section: Metallaphotoredox Catalysis: C–c Bond Formationmentioning
confidence: 99%
“…The method exhibited a broad substrate scope and good functional group tolerance, and an array of ortho ‐substituted acylacetanilides were prepared in high yields under mild conditions. Subsequently, the same group described another decarboxylative ortho ‐acylation of azo‐ and azoxybenzenes 127 by using a combination of palladium catalysis and visible‐light photoredox catalysis in the presence of organic catalyst 129 at room temperature under 1.5 W of blue LED irradiation (Scheme b) …”
Section: Formation Of C−c Bondsmentioning
confidence: 99%
“…The azoor azoxy-benzenes could also engage in the aryl C−H acylation by dual catalysis with 9-mesityl-10-methylacridinium (Mes-AcrPh) as the photocatalyst, and the presence of O 2 · − was detected by EPR analysis (Scheme 7b). 24 …”
Section: Decarboxylative Functionalizationmentioning
confidence: 97%